Desquamation mechanism of the gothic preterite-present verb origin - Botsman, Andriy; Dmytruk , Olga; Bondarenko , Valeria (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article describes the attempt to process reconstruction which caused the formation of the preterite-present verb subgroup in the Gothic language. The reconstruction was based on the primary supposition of relationship and correlation of the preterite-present subgroup and the group of the strong verbs. That relationship is understood as the reconstruction of ablaut fragments belonging to the strong verbs, preterite with the further reflection of ablaut fragments in the preterite-present verbs, presence. The preterite-present verbs were separated into the individual subgroup involving the mechanism of desquamation. It is recognized as a gradual, multi-stage exfoliation, come off in layers of preterite-present verbs-to-be from the strong verb corpus.The desquamation was understood as an integrated phenomenon which got definite outlines owing to the fact that the quality parameters were introduced. They gave the opportunity of desquamation describing using the quantitative indices. They permitted to describe desquamation in an objective way. The manifestation of desquamation features is associated with the degree of feature displayed. The quantitative parameter is recognized as penetrance. The opposite parameter is understood as a degree of feature lack. It is recognized as expressiveness. Both of them (penetrance and expressiveness) outline borders within which desquamation features exist and function; they act as self correlates. The desquamation descriptive precision becomes higher after the introduction of supplementary quantitative parameters. Mutual relations between strong and preterite-present verbs can be calculated with the number of ligaments. They form the notion of ligamentation. From another point of view, the number of calculated ligaments helps to describe ligamentation as menodentated or bidentated. In particular, a bidentated ligamentation may be classified as homogeneous of heterogeneous, taking into consideration nature of ligaments.The system of quantitative parameter usage enables to subdivide Gothic preterite-present verbs into two quasi-groups. The first quasi-group contains verbs have definite correlations with the strong verbs of certain ablaut classes. The second one grasps verbs having obscure correlations with the certain ablaut classes. Obscure correlations demonstrate very indefinite connection with two ablaut classes simultaneously. It indicates the intermediate location of three preterite-present verbs (the second quasi-group) between two ablaut classes. That oscillation between two ablaut classes complicated the process of desquamation. The desquamation is connected with translocation, which designates the process when the verb desquamated from the corpus of strong verbs is shifted into the system of preterite-present verb parameters.Tendencies fixed in the system of quantitative parameters are connected with the Gothic language, and may be used for further Common-Germanic generalization. It looks promising to research the preterite-present verbs in the North-Germanic and West-Germanic areas with finding out their difference, similarity, and individual specification.
Keywords: ablaut class, desquamation, ligamentation, penetrance, preterite-present verb, translocation.